THE EFFECT OF COMPETENCE, JOB TRAINING, CAREER DEVELOPMENT AND SUPERVISION ON THE PERFORMANCE OF INDOMARET EMPLOYEES IN EAST BEKASI (CASE STUDY OF RITAIL COMPANY) - Risqi Nur Parwati; Muhammad Richo Rianto; Eri Bukhari; Rinjani (Draf Solusi Indonesia, 2023)
This study aims to measure the direct and indirect influence of competence, job training, career development and insight into the performance of Indomaret employees in East Bekasi (case study of a real company). The results of this study provide an explanation that competency variables have a positive and significant effect on employee performance, job training has a positive and significant effect on employee performance, supervision has a positive and significant effect on employee performance. However, the direct influence of career development has no effect on employee performance.